Dakwah Multikultural Dalam Lembaga Pendidikan - Tanuri (Ad-DA'WAH, 2023)
The findings from this research confirm that multicultural education in the view of the Qur'an does not conflict with the Islamic system in all its aspects and especially Islam as a source of law. The differences that exist are precisely as assets for scholars to study them, as a scientific discourse. Through multicultural education, it is hoped that each individual and group will accept and appreciate the differences that exist, live side by side in harmony in order to create a peaceful society and a united nation. Another interesting discovery from this research is that Islam teaches the importance of unity, brotherhood, respect for diversity, respect for human values, the desire to form a harmonious and just society and the importance of respecting all people. In fact, several characteristics are formed by the verses of the Al-Qur' interpretation and interpretation as a reference that shows the concept of multicultural education parallel to Islamic teachings governing the structure of human beings living on earth, especially in the context of education.